The medium is the message… Also, in the academy? Exploring the influence of environment policy think tanks - Vanessa Roger-Monzó; Fernando Castelló-Sirvent (Frontiers in Political Science)
This research aims to analyze how think tanks influence scholars’ academic debate. Specifically, the influence strategies followed by think tanks specialized in environmental policy through funding scientific articles in high-impact academic journals are examined. Articles published between 2008 and 2023 (n = 3,502) in scientific journals indexed in Journal Citation Reports (JCR) according to the Science Social Sciences Citation Index (SSCI) and Science Citation Index Expanded (SCIE) were analyzed. Their impact was assessed in terms of number of citations (n = 124,933) and Normalized Impact per Year (NIY). Two sub-periods were constructed, before and after the start of the 2030 Agenda, to analyze the academic influence strategies of think tanks specialized in the study area, analyzing co-funding strategy and the most notable changes in the areas of interest and preference for funding think tanks. VOSviewer 1.6.20 was used to analyze the corpus of scientific publications in both periods. The results suggest that think tanks use financing for scientific research to boost their presence and influence in the academic debate. This trend intensified after the start of the 2030 Agenda, and several think tanks detected co-financing strategies. This exploratory study represents a novelty in the literature on the academic influence of think tanks. The main contribution of this article is to propose an analysis methodology that can be replicated in other areas of study and to offer evidence on the impact strategies of think tanks in the academic debate.